Russian Federation : 2020 Article IV Consultation-Press Release; Staff Report. (International Monetary Fund, 2021)
Russia entered the crisis with low potential growth but strong macroeconomic policy frameworks and significant buffers. Policy space allowed the authorities to mount a sizeable public health and countercyclical response to the crisis, which has helped limit the economic downturn. Nevertheless, the crisis is likely to leave some long-term scars.